Penerapan Model Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kritis dan Bekerja Sama Peserta Didik pada Mata Pelajaran Fikih MA Al-Kautsar Pekanbaru - Awwalul 'Abidin; Hidayati Hidayati; Rivdya Eliza (Al-Munawwarah : Jurnal Pendidikan Islam, 2025)
This study is motivated by the low levels of critical thinking and collaboration skills among eleventh-grade students at MA Al-Kautsar Pekanbaru, which have negatively affected their learning outcomes in Fiqh. The learning process has been predominantly teacher-centered with one-way interactions, minimal material analysis, and a lack of group collaboration. The objective of this research is to describe the implementation of the Problem-Based Learning (PBL) model in enhancing students' critical thinking and collaboration skills. The study employed a quasi-experimental method using a randomized control group only design. The sample consisted of class XI-A (25 students) as the experimental group taught using the PBL model, and class XI-B (32 students) as the control group taught using conventional methods. Data collection techniques included tests, questionnaires, and observations. The results showed that: (1) the average critical thinking score of students in the experimental group was 84.00, higher than the control group’s 62.66, with a t-value of 10.247 > t-table value of 2.004; and (2) the average collaboration skill score in the experimental group was 81.56, compared to 64.88 in the control group, with a t-value of 5.359 > t-table value of 2.004. In conclusion, the PBL model is effective in improving students' critical thinking and collaboration skills in Fiqh learning.Keywords: Problem-Based Learning, critical thinking skills, student collaboration, Fiqh.